The Effect of Thymosin beta4 on the Survival of Autologous Fat Grafting: A Preliminary Study. (7th March 2020) - Qu, Yaping; Wang, Qian; Fu, Su; Guo, Xiaoshuang; Luan, Jie; Mu, Dali
Abstract: Background: Autologous fat grafting is a common procedure to improve tissue deficiencies. However, the survival rate of fat grafting is unpredictable. Thymosin beta 4 (Tß4), a multifunctional peptide containing 43 amino acids, is effective in angiogenesis, inhibiting apoptosis and inflammation. Objectives: The authors initially investigated the potential effect of Tß4 in fat grafting. Methods: Adipose tissue premixed exogenous Tß4 were transplanted into rabbit ears. Rabbits were randomly assigned to 3 groups: group A, 5 μg/mL Tß4; group B, 10 μg/mL Tß4; and group C, phosphate-buffered saline buffer as a blank control. The fat grafts were subjected to magnetic resonance imaging at 2, 4, and 12 weeks in vivo. Each harvested graft was analyzed at 3 time points after transplantation. Results: The fat grafts in the Tß4-treated groups showed better volume and weight retention, greater adipose tissue integrity, adipocyte viability, and angiogenesis. The results of dynamic contrast-enhanced magnetic resonance imaging also showed that the experimental groups increased microcirculation perfusion of the grafts. Conclusions: The study proved that Tß4 could improve adipose tissue survival and neovascularization. It may be useful for fat grafting as a potential protective reagent.